1999
DOI: 10.1128/iai.67.6.2804-2809.1999
|View full text |Cite
|
Sign up to set email alerts
|

CD4 + T Cells and the Proinflammatory Cytokines Gamma Interferon and Interleukin-6 Contribute to Alveolar Bone Loss in Mice

Abstract: In this study, we used a mouse model to examine the role of the adaptive immune response in alveolar bone loss induced by oral infection with the human gram-negative anaerobic bacteriumPorphyromonas gingivalis. Severe combined immunodeficient mice, which lack B and T lymphocytes, exhibited considerably less bone loss than did immunocompetent mice after oral infection, suggesting that lymphocytes contribute to this process. Bone loss after oral infection was decreased in mice deficient in major histocompatibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
219
0
5

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 310 publications
(237 citation statements)
references
References 43 publications
12
219
0
5
Order By: Relevance
“…In regards to alveolar bone loss, we have previously shown that deletion of CD4 þ T cells, but not of CD8 þ T cells, abrogates bone loss after bacterial infection [13]. Teng and colleagues have also shown alveolar bone loss attributable to CD4 þ T cells [14].…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In regards to alveolar bone loss, we have previously shown that deletion of CD4 þ T cells, but not of CD8 þ T cells, abrogates bone loss after bacterial infection [13]. Teng and colleagues have also shown alveolar bone loss attributable to CD4 þ T cells [14].…”
Section: Discussionmentioning
confidence: 97%
“…P. gingivalis induces secretion of these cytokines [25^27]. Knockout mice missing either IL-6 or IFG do not lose alveolar bone after oral infection with P. gingivalis, while genetically matched wild-type strains do lose bone [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to recent pathogenetic models genetic factors causing imbalances in pro-and anti-inflammatory cytokine production along with an ineffective immune response against bacterial invasion were suggested to increase the susceptibility for periodontitis [22]. Among others interleukin-16 was shown to be involved in the regulation of the expression of several proinflammatory cytokines by cells of the monocyte/macrophage system [16].…”
Section: Discussionmentioning
confidence: 99%